Modelagem e análise da rugosidade superficial do aço ABNT 1045 tratado termicamente - Silva, Edleusom Saraiva da (2017)
The machining processes are widely used in the industrial environment and aim to change the dimensions of a piece. At present, any improvements made to the machine, material, tool or process can lead to a reduction in manufacturing cost. The surface finish of each manufactured piece must be adequate according to the function that it will exert, thus, the surface roughness is of high importance when the requirements of the project grow. This work aims to analyze and model the surface roughness of ABNT 1045 steel under different metallurgical conditions. For the accomplishment of the experiments the steel was machined with tools of hard metal class P with covering. A factorial design 2² was used in the development of the experiments. As influencing variables, the feed, and nose radius of the tool were analyzed; the response variables were the surface roughness parameters Ra and RT. A commercial software was used for the development of mathematical models through the design of experiments (DOE) and for analysis of variance (ANOVA) for a confidence of 95% in the results. The results showed that the metallurgical state of the part has influence on the roughness; The behavior of the roughness in the steel as received and in the normalized steel did not follow what is generally described in the literature and that the mathematical models developed are promising to predict and estimate surface roughness, since they were more accurate than the theoretical models obtained in the literature.